The Convention for the Protection of Human Rights and Fundamental Freedoms as an International Treaty and a Source of Individual Rights - Gadkowski, Aleksander (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2021)
The aim of this paper is to present the legal nature of the Convention for the Protection of Human Rights and Fundamental Freedoms as a special treaty under international human rights law. The article focuses on the twofold nature of the Convention. First, it presents the Convention as an international treaty, and thus as a source of specific obligations of states-parties. Second, it presents the Convention as the source of fundamental individual human rights. The article also discusses the role of ECtHR case law in the context of fundamental individual human rights.